Transcription factor A, mitochondrial promotes lymph node metastasis and lymphangiogenesis in epithelial ovarian carcinoma - Wubuli Reziwanguli; Niyazi Mayinuer; Han Lili; Aierken Mayinuer; Fan Lingling (Open Medicine)
Mitochondria play a central, multifunctional role in cancer progression. However, the mechanism of mitochondrial genes in epithelial ovarian cancer (EOC) remains unclear. This study aimed to screen candidate mitochondrial genes in EOC and then to investigate their biological functions and potential mechanisms.